Anti-PD-1 Immunotherapy and Radiotherapy for Stage IV Intrahepatic Cholangiocarcinoma: A Case Report - Liu, Ze-Long; Liu, Xin; Peng, Hong; Peng, Zhen-Wei; Long, Jian-Ting; Tang, Di; Peng, Sui; Bao, Yong; Kuang, Ming (Frontiers in Medicine, 2020)
Due to the unsatisfactory robustness of current predictive biomarkers in many cases, application of immunotherapy in advanced cancers with limited treatment options, such as stage IV intrahepatic cholangiocarcinoma (ICC) was quite common in real world. Hence, strategies to enhance therapeutic effect of immunotherapy or to extend the scope of potential beneficial patients were urgently needed. Combination of radiotherapy and anti-programmed death receptor-1 (PD-1) immunotherapy was a promising one since they were found to have synergistic anti-tumor effect in animal models and a couple of patients. We here present a 68-year-old male with chemotherapy-intolerable stage IV ICC, whose primary tumor had low PD-L1 expression level, scarce CD8+ cells in tumor microenvironment, high microsatellite instability (MSI), and high tumor mutation burden (TMB). These biomarkers here showed conflicting prediction of treatment response and clinical benefit of anti-PD-1 immunotherapy. Combination therapy of anti-PD-1 immunotherapy and radiotherapy was adopted as first-line treatment for the patient. After 6 cycles of immunotherapy, shrinkage of the primary liver tumor and metastatic lymph nodes happened, alongside with new lung metastasis, which indicated a mixed response. Radiotherapy was then administered to both of the liver and lung lesions, accompanied with continued immunotherapy. The combined therapy eventually led to a complete response for both of the primary tumor and all metastases without treatment-related adverse effects. The patient has survived for 26 months after the combined therapy and remains tumor-free currently. This case demonstrates the high inconsistency between immunotherapy response biomarkers and the synergetic anti-tumor effect of immunotherapy and radiotherapy in ICC.